Production Plan of Home Scale Tomato Kefir - Wignyanto, Wignyanto; Nurika, Irnia; Vida, Ike (Jurnal Teknologi Pertanian, 2007)
Tomato kefir is made by fermenting tomato using kefir cultures, which were considered as probiotics.  This research was aimed to find out the concentration of sucrose and the appropriate length of fermentation in making tomato kefir, and to gain the projection of which home industry scale production was financially feasible.  The Randomized Block Design was in the experiment assessing the above-mentioned two factors. The results indicated that the best tomato kefir may be obtained by addition of the sucrose at a level of 12.5% and 48 hours fermentation. Production planning for home industry scale of the tomato kefir was advised to be carried out at a production capacity of 15 liters/day which was packed in 60 ml/bottle each. At the scale, 4 employees were need.  It was found out that the cost was Rp. 600/bottle.  With the expected profit as much as 20%, so the selling price must be Rp. 1.100.  The calculation of BEP shows that the company will be paid off after selling 35.961 bottles, equal with Rp. 36.575.785.  The investment will be returned in less than 1 year.Key words: production planning, kefir, tomato